1983
DOI: 10.3171/jns.1983.58.2.0231
|View full text |Cite
|
Sign up to set email alerts
|

Failure of prophylactically administered phenytoin to prevent early posttraumatic seizures

Abstract: A randomized double-blind placebo-controlled study was carried out to determine whether phenytoin administered soon after injury lessens the incidence of epilepsy in the 1st week after severe head trauma. In this study, 244 patients were randomized into either a phenytoin or placebo group. The patients in the phenytoin group were administered phenytoin intravenously or intramuscularly within 24 hours of hospital admission. Patients in the placebo group received intravenous or intramuscular diluent. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
2
2

Year Published

1983
1983
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(69 citation statements)
references
References 15 publications
1
64
2
2
Order By: Relevance
“…11 The other class I study, which evaluated a similar phenytoin regimen in a smaller but similar cohort, found no significant difference. 10 The latter study, however, reported a rate of early seizures in the placebo group of only 3.7%, which is much lower than the rates seen in other studies. Because the absolute seizure rates are so low in this study, the 95% CI for the RR (0.27 to 3.58) is very wide.…”
mentioning
confidence: 60%
See 3 more Smart Citations
“…11 The other class I study, which evaluated a similar phenytoin regimen in a smaller but similar cohort, found no significant difference. 10 The latter study, however, reported a rate of early seizures in the placebo group of only 3.7%, which is much lower than the rates seen in other studies. Because the absolute seizure rates are so low in this study, the 95% CI for the RR (0.27 to 3.58) is very wide.…”
mentioning
confidence: 60%
“…In the class I study demonstrating no significant benefit of prophylaxis, more than 78% of patients maintained therapeutic levels through the first week, although only 60% of those who had an early seizure had a therapeutic level immediately afterward. 10 In the class II study evaluating carbamazepine, average serum AED levels in the first week were in the therapeutic range. 12 In the class III study, levels were checked and doses adjusted accordingly but specific figures were not reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Posttraumatic convulsions not only aggravate secondary injury to the brain after initial insult by increasing the intracranial pressure and hypoxia, but also make monitoring the head injured patients more difficult due to postictal neurological deterioration. This might lead to delay in the treatment of intracranial mass lesion [3]. Posttraumatic seizures have been the subject of investigation in a number of studies, mainly concerned with adults [2, 3, 4, 5, 6].…”
Section: Introductionmentioning
confidence: 99%